2016
DOI: 10.1080/13811118.2016.1222318
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of the Columbia-Suicide Severity Rating Scale for Short-Term Suicidal Behavior: A Danish Study of Adolescents at a High Risk of Suicide

Abstract: Using the Columbia-Suicide Severity Rating Scale (C-SSRS), we examined the predictive and incremental predictive validity of past-month suicidal behavior and ideation for short-term suicidal behavior among adolescents at high risk of suicide. The study was conducted in 2014 on a sample of 85 adolescents (90.6% females) who participated at follow-up (85.9%) out of the 99 (49.7%) baseline respondents. All adolescents were recruited from a specialized suicide-prevention clinic in Denmark. Through multivariate log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 28 publications
(47 reference statements)
0
29
0
5
Order By: Relevance
“…Non-suicidal self-injurious and suicidal behaviors. The Colombia Suicide Severity Rating Scale (C-SSRS) (Conway et al, 2017;Gipson et al, 2015;Posner et al, 2011) is a semi-structured interview used to measure suicide ideation and behavior. The scale consists of four subscales, each rated separately: severity of ideation (score ranges between 0 and 5), intensity of ideation, behavior subscale, and behavior lethality.…”
Section: Methodsmentioning
confidence: 99%
“…Non-suicidal self-injurious and suicidal behaviors. The Colombia Suicide Severity Rating Scale (C-SSRS) (Conway et al, 2017;Gipson et al, 2015;Posner et al, 2011) is a semi-structured interview used to measure suicide ideation and behavior. The scale consists of four subscales, each rated separately: severity of ideation (score ranges between 0 and 5), intensity of ideation, behavior subscale, and behavior lethality.…”
Section: Methodsmentioning
confidence: 99%
“…The sixth and last item on the tool asks about any lifetime history of preparations and/or plans to end one's life, and if yes, whether these have been done in the last six months. We could find only one specific validation study of the C-SSRS -Screen Version (The Columbia Lighthouse Project, n.d.) among adults (Wilson, 2017), although the longer risk assessment version of the C-SSRS has been validated across several settings and among children and adolescents (see below) Conway, Erlangsen, Teasdale, Jakobsen, & Larsen, 2016;Gipson, Agarwala, Opperman, Horwitz, & King, 2015;Horwitz, Czyz, & King, 2015;Posner et al, 2011). There is a version of the C-SSRS Screener with triage points for schools (Heise, York, & Thatcher, 2016; The Columbia Lighthouse Project, n.d.) suggesting its applicability to an adolescent population.…”
Section: Screening Toolsmentioning
confidence: 99%
“…The suicidal behaviour and actual attempt section consists of yes/no answers related to actual attempts, self-injurious behaviour, interrupted and aborted attempts, preparatory acts or behaviours, and lethality (Posner et al, 2011). Strengths of the C-SSRS include that it has been used and validated with adults and adolescents (Gipson et al, 2015;Posner et al, 2011), and been found to predict short-term suicidal behaviour among high-risk adolescents (Conway et al, 2016). Despite the C-SSRS' promise, several authors have noted challenges with classifying both intent and imminence (Interian et al, 2018), and with implementation (e.g.…”
Section: Suicide Risk Assessment Overviewmentioning
confidence: 99%
“… 3 Deterrents to suicide include mental fitness, frustration tolerance, cognitive abilities, coping skills, parenthood, supportive relationships, community and other social connections, purpose, ethical and religious beliefs, good medical and neurological health, and access to social services and psychiatric and medical care. 4 …”
Section: Introductionmentioning
confidence: 99%